Anthocyanins in the diet of children : Intake estimations and sensory evaluation of relevant foods - Drossard, Claudia; Justus Liebig University Giessen (My University, 2012)
Anthocyanins are orange to blue coloured secondary plant metabolites that are present in plant foods and might contribute to the prevention of chronic diseases, such as cancer and cardiovascular disease. From a public health point of view, a health-promoting diet is particularly important in childhood, as food preferences and dietary habits may be established during this period and maintained into adulthood.The aims of this thesis were to assess anthocyanin intake (as aglycones, called anthocyanidins), sources of anthocyanins, and trends with age and time of anthocyanidin density of the diet of infants and toddlers (0-3 years), and children and adolescents (4-18 years) from 1990-2009, and to examine the liking of anthocyanin-rich juices and smoothies (whole fruit drinks) in 4-17-year-olds as potential products to increase anthocyanin intake.Within the scope of the BMBF joint research project ANTHONIA, this thesis used the existing data and structure of the longitudinal DONALD Study - specifically the regular 3-day weighed dietary records for anthocyanin intake estimations and the participants regular visits to the Research Institute of Child Nutrition for the purpose of conducting hedonic sensory testings. Anthocyanin content data were taken from the USDA Database for the Flavonoid Content of Selected Foods. However, the anthocyanidin content values for bananas and nuts provided by the USDA have been excluded, because they base on an unsuitable analytical method. The anthocyanin-rich products were produced by the Geisenheim Research Center.Anthocyanins were widely present in the diet from late infancy onwards. Pomaceous fruit (pears, apples) were the main source in infancy and strawberries in the older age groups. Anthocyanidin density increased during infancy and decreased thereafter. Over the 20 years, density decreased in infants, slightly increased in toddlers (18-36 months) and decreased in the first half, but increased in the second half of the study period in children and adolescents. Density was higher in girls than in boys during childhood and adolescence. Anthocyanin-rich products, in particular grape-bilberry juice, were well-liked. Juices were liked better than smoothies and grape-bilberry better than apple-bilberry mixtures. A subgroup of participants rated smoothies higher than juices and/or apple-bilberry higher than grape-bilberry mixtures.In conclusion, there is scope to increase the anthocyanidin density of children s diets, particularly with increasing age and in boys, and grape-bilberry juice is a promising product with which to achieve this. To finally deduce and implement evidence-based dietary recommendations, research firstly on the efficacy of anthocyanins, and secondly on food development and marketing strategies to reach children and adolescents, is fundamental.

Anthocyane sind orange- bis blau-farbige sekundäre Pflanzenstoffe in pflanzlichen Lebensmitteln die zur Prävention chronischer Krankheiten wie Krebs und Herzkreislauferkrankungen beitragen könnten. Aus Sicht der Volksgesundheit (Public Health) ist eine gesundheitsfördernde Ernährungsweise besonders in der Kindheit wichtig, da Lebensmittelvorlieben und Ernährungsgewohnheiten in dieser Zeit geprägt und bis ins Erwachsenenalter beibehalten werden könnten.Ziele dieser Doktorarbeit waren daher, Anthocyanaufnahme (als Aglykone, Anthocyanidine genannt), -quellen sowie Alters- und Zeitverläufe der Anthocyanidindichte der Nahrung bei Säuglingen und Kleinkindern (0-3 Jahre) sowie bei Kindern und Jugendlichen (4-18 Jahre) von 1990-2009 zu ermitteln und die Beliebtheit anthocyanreicher Säfte und Smoothies (Ganzfruchtgetränke) bei 4-17jährigen zu untersuchen, als mögliche Produkte zur Erhöhung der Anthocyanzufuhr in dieser Altersgruppe.Im Rahmen des BMBF-Verbundprojekts ANTHONIA wurden für die vorliegende Doktorarbeit vorhandene Daten und Struktur der Langzeitstudie DONALD genutzt, im Besonderen die regelmäßigen 3-Tage-Wiege-Ernährungsprotokolle für die Anthocyanaufnahmeschätzung, und die regelmäßigen Besuche der Teilnehmer am Forschungsinstitut für Kinderernährung zur Durchführung hedonischer sensorischer Tests. Daten zum Anthocyangehalt von Lebensmitteln wurden der USDA Database for the Flavonoid Content of Selected Foods entnommen, wobei die darin enthaltenen Anthocyanidinwerte für Bananen und Nüsse ausgeschlossen wurden, da sie auf einer ungeeigneten Analysemethode beruhen. Die anthocyanreichen Produkte wurden von der Forschungsanstalt Geisenheim produziert.Anthocyane waren vom Säuglingsalter an in der Nahrung weit verbreitet. Kernobst (Äpfel, Birnen) war die Hauptquelle bei Säuglingen, Erdbeeren in den älteren Altersgruppen. Die Anthocyanidindichte der Nahrung stieg im Säuglingsalter an und fiel danach ab. Über die 20 Jahre sank die Anthocyanidindichte bei Säuglingen, stieg bei Kleinkindern (18-36 Monate) leicht und sank in der ersten, aber stieg in der zweiten Hälfte der Studienperiode bei Kindern und Jugendlichen. Die Dichte war in Kindheit und Jugend bei Mädchen höher als bei Jungen. Anthocyanreiche Produkte, besonders Traube-Heidelbeersaft, waren sehr beliebt, dabei Säfte beliebter als Smoothies und Traube-Heidelbeer- beliebter als Apfel-Heidelbeermischungen. Eine Untergruppe von Teilnehmern bewertete Smoothies besser als Säfte und/oder Apfel-Heidelbeer- besser als Traube-Heidelbeermischungen.Schlussfolgernd lässt sich sagen, dass es Spielraum zur Erhöhung der Anthocyanidindichte der Nahrung bei Kindern gibt, insbesondere mit steigendem Alter und bei Jungen, und dass Traube-Heidelbeersaft ein vielversprechendes Produkt hierfür ist. Um letztendlich evidenzbasierte Ernährungsempfehlungen abzuleiten und umzusetzen, ist Forschung zum Einen zur Wirksamkeit der Anthocyane und zum Anderen zu Produktentwicklung und Marketingstrategien zur Erreichung von Kindern und Jugendlichen grundlegend.
Anthocyane in der Kinderernährung : Aufnahmeschätzungen und sensorische Bewertung relevanter Lebensmittel
Keywords: Anthocyane; Kinder; Aufnahmeschätzung; sensorische Bewertung; Saft; anthocyanins; children; intake estimation; sensory evaluation; juice; ddc:640